Comparative Analysis of Route and Health Care Facilities for the Emergency Patients of Pune and Bengaluru - Adwait Priyadarshan; Manish Kumar Mishra (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2026)
Abstract. A comparative analysis of timely medical admission for emergency patients in two mega cities of India, Bengaluru and Pune has been analyzed using geo informatics based open-source tools. The road network has been initially classified as primary, secondary, tertiary and service categories. These categories have been merged into a single layer for homogeneous routes for the cities. To visualize the effect of traffic congestion the TomTom traffic data was downloaded as GeoJSON file, later converted into geo-package (GPKG). The traffic file was joined to the non-traffic merged file to assign the congestion index to the segments. Both traffic integrated and free-flow isochrones were created for 5, 10 and 15 minutes. Service area and population coverage under these isochrones were evaluated after converting isochrones into concave hull. The grid network and redundancy of Bengaluru reflects a resilient sponge with efficient elimination of penalty (nominal 1.34 %) for population coverage in 15 minutes using the available detours. Due to the dendritic road network of Pune, compensation in congestion is significantly low and impact remains high (demographic penalty of 5.14%) leaving a large population vulnerable for emergencies even after 15 minutes. The road redundancy of Bengaluru is capable of largely absorbing congestion, on contrary, the morphological constraints pose a challenge for Pune leading to vulnerability in emergency medical access support.